Root Canal Microorganisms Profiles of Upper Anterior Teeth with Periapical Lesion - Tanumihardja, Maria; Riewpassa, Irene E.; Nasir, Mansjur; Pasiga, Burhanuddin D. (Journal of Dentistry Indonesia, 2014)
Microorganisms are the main causative agents on the development of apical periodontitis. Microorganisms infecting the root canal system are colonized in communities as biofilm. These bacterial communities show distinct pattern related to the different forms of apical periodontitis which are determined by species richness and abundance. Objective: This study is aimed to examine the root canal microorganisms on upper anterior teeth of asymptomatic apical periodontitis and chronic apical abscess. Methods: Samples were collected from patients referred to Endodontic Department of Hasanuddin University Dental Hospital from July 2013 to September 2013. Twenty two samples, aged 17-40 were collected from 16 patients with asymptomatic apical periodontitis, and 36 samples, aged 18-50 were collected from 36 patients with chronic apical abscess. Microorganisms were evaluated using cultural technique. Results: The results showed predominant bacteria in asymptomatic apical periodontitis is Porphyromonas spp while in chronic apical abscess both Streptococcus spp and Porphyromonasspp showed similar frequencies. This study showed Porphyromonas spp plays dominant role in apical periodontitis either in asymptomatic apical periodontitis or chronic apical abscess. Conclusion:This study showed different composition of bacteria within different apical periodontitis and Porphyromonas spp is the most prevalent bacteria found in both asymptomatic apical periodontitis and chronic apical abscess.